The N34S mutation of SPINK1 (PSTI) is associated with a familial pattern of idiopathic chronic pancreatitis but does not cause the disease. Issue 5 (1st May 2002) - Threadgold, J; Greenhalf, W; Ellis, I; Howes, N; Lerch, M M; Simon, P; Jansen, J; Charnley, R; Laugier, R; Frulloni, L; Oláh, A; Delhaye, M; et al.
Abstract : Background: Mutations in the PRSS1 gene explain most occurrences of hereditary pancreatitis (HP) but many HP families have no PRSS1 mutation. Recently, an association between the mutation N34S in the pancreatic secretory trypsin inhibitor (SPINK1 or PSTI) gene and idiopathic chronic pancreatitis (ICP) was reported. It is unclear whether the N34S mutation is a cause of pancreatitis per se, whether it modifies the disease, or whether it is a marker of the disease. Patients and methods: A total of 327 individuals from 217 families affected by pancreatitis were tested: 152 from families with HP, 108 from families with ICP, and 67 with alcohol related CP (ACP). Seven patients with ICP had a family history of pancreatitis but no evidence of autosomal dominant disease (f-ICP) compared with 87 patients with true ICP (t-ICP). Two hundred controls were also tested for the N34S mutation. The findings were related to clinical outcome. Results: The N34S mutation was carried by five controls (2.5%; allele frequency 1.25%), 11/87 (13%) t-ICP patients (p=0.0013 v controls), and 6/7 (86%) affected (p<0.0001 v controls) and 1/9 (11%) unaffected f-ICP cases. N34S was found in 4/108 affected HP patients (p=0.724 v controls), in 3/27 (11%) with wild-type and in 1/81 (1%) with mutant PRSS1, and 4/67 ACP patients (all p>0.05 v controls). The presence of the N34S mutation was not associated with early disease onset or disease severity. Conclusions: The prevalence of the N34S mutation was increased in patients with ICP and was greatest in f-ICP cases. Segregation of the N34S mutation in families with pancreatitis is unexplained and points to a complex association between N34S and another putative pancreatitis related gene.